Pattani central mosque in Southern Thailand as sanctuary from violence - Ridwan Ridwan (IAIN Salatiga, 2014)
This article describes the real quality of Pattani Central Mosque to depict another picture of mosques in southern Thailand that has been alleged as an arena for the spreading of Islamic radical ideas and the recruiting of young people into ‘martyrs’ against the Thai Government. It is not doubted, the 2004 Kru-ze Mosque incident reflects the failure of places of worship as a‘sanctuary from violence’. Consequently, there are questions about the kind of practices taking place in Islamic teaching, mosque management, and the views held by mosque stakeholders (Imam, the preachers, and congregation) toward good governance, human rights and the anticipation of radicalism given the current situation in Pattani. In sum, Pattani Central Mosque instead seems to be composed of a fairly equal mixture of moderate and more conservative believers rather than those with radical and extreme tendencies. Artikel ini mendeskripsikan kualitas yang nyata dari Masjid Raya Pattani untuk mengilustrasikan gambaran lain tentang masjid-masjid di Thailand Selatan yang disinyalir sebagai arena penyebaran ide-ide Islam radikal dan rekruitmen orang–orang muda sebagai “martir” melawan Pemerintah Thailand. Tidak terbantahkan, insiden Masjid Kru-ze tahun 2004 merefleksikan kegagalan tempat-tempat ibadah sebagai ‘sanctuary from violence’. Akibatnya, terdapat sejumlah pertanyaan mengenai jenis-jenis praktik pengajaran, manajemen masjid dan pandangan dari para pengelola/takmir masjid (Imam, juru dakwah, and jemaah) terhadap pemerintahan yang baik, hak asasi manusia dan antisipasi atas radikalisme di Pattani dewasa ini. Sebagai kesimpulan, Masjid Raya Pattani tampaknya lebih terbentuk oleh gabungan para pengikut yang moderat dan lebih konservatif dibandingkan mereka yang memiliki tendensi-tendensi radikal dan ekstrem.